cos(x)+cos(y)=3/4 x+y=2*p*1/3

Дано

$$\cos{\left (x \right )} + \cos{\left (y \right )} = \frac{3}{4}$$

2*p
x + y = —
3

$$x + y = \frac{2 p}{3}$$
Ответ
$$p_{1} = \frac{3 y}{2} + \frac{3}{2} {acos}{\left (- \cos{\left (y \right )} + \frac{3}{4} \right )}$$
=
$$\frac{3 y}{2} + \frac{3}{2} {acos}{\left (- \cos{\left (y \right )} + \frac{3}{4} \right )}$$
=

1.5*y + 1.5*acos(3/4 — cos(y))

$$x_{1} = {acos}{\left (- \cos{\left (y \right )} + \frac{3}{4} \right )}$$
=
$${acos}{\left (- \cos{\left (y \right )} + \frac{3}{4} \right )}$$
=

acos(3/4 — cos(y))

$$p_{2} = \frac{3 y}{2} — \frac{3}{2} {acos}{\left (- \cos{\left (y \right )} + \frac{3}{4} \right )} + 3 \pi$$
=
$$\frac{3 y}{2} — \frac{3}{2} {acos}{\left (- \cos{\left (y \right )} + \frac{3}{4} \right )} + 3 \pi$$
=

9.42477796076938 + 1.5*y — 1.5*acos(3/4 — cos(y))

$$x_{2} = — {acos}{\left (- \cos{\left (y \right )} + \frac{3}{4} \right )} + 2 \pi$$
=
$$- {acos}{\left (- \cos{\left (y \right )} + \frac{3}{4} \right )} + 2 \pi$$
=

6.28318530717959 — acos(3/4 — cos(y))

1 Звезда2 Звезды3 Звезды4 Звезды5 Звезд (Пока оценок нет)
Загрузка...